Work-Life Conflict of Native and Immigrant Entrepreneurs in South Africa - Fatoki, Olawale (Journal of Economics and Behavioral Studies, 2018)
Work life conflict negatively impacts entrepreneurs and the economic performance of their businesses. The study explored the work-life conflict (WLC) of native and immigrant entrepreneurs in South Africa. Also, the study examined the effect of gender and work-related factors (long working hours and work overload) on the WLC of native and immigrant entrepreneurs. The study adopted the survey method (selfadministered questionnaires) for data collection. The participants in the study were identified through convenience and snowballing sampling methods. The methods of data analysis included descriptive statistics, T-test, Pearson correlation and regression analysis. The results showed high levels of WLC for both native and immigrant entrepreneurs. Native entrepreneurs have a higher level of WLC compared to immigrant entrepreneurs, however the difference is not statistically significant. Male entrepreneurs have a lower level of WLC compared to female entrepreneurs. Long working hours and work overload significantly impact on the WLC of native and immigrant entrepreneurs. Recommendations to reduce WLC include goal setting, scheduling and delegation of work by entrepreneurs.